2021
DOI: 10.1097/tp.0000000000003472
|View full text |Cite
|
Sign up to set email alerts
|

Is 0.6% Reasonable as the Minimum Requirement of the Graft-to-recipient Weight Ratio Regardless of Lobe Selection in Adult Living-donor Liver Transplantation?

Abstract: Original Clinical Science-Liver Background. Several studies reported favorable outcomes of small-for-size grafts with graft-to-recipient weight ratio (GRWR) <0.8% in living-donor liver transplantation (LDLT). However, their indications should be carefully determined because they must have been indicated for low-risk cases over larger grafts with 0.8% ≤ GRWR. Furthermore, evidence for minimum requirements of GRWR remains inconclusive. We investigated the safety of small-for-size grafts against larger grafts by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 52 publications
3
37
1
Order By: Relevance
“…Also, postreperfusion splenectomy was performed based on graft hemodynamics regardless of graft type and size. A similar approach has been reported by others, with splenectomy rates of 80% of RLG (H5678)-LDLT in the Kyushu group and 61% of LDLT with GRWR >0.8% in the Kyoto group 12,40. In contrast, PCS41 and SAL42 have been widely utilized in Western countries 17.…”
Section: Discussionsupporting
confidence: 58%
“…Also, postreperfusion splenectomy was performed based on graft hemodynamics regardless of graft type and size. A similar approach has been reported by others, with splenectomy rates of 80% of RLG (H5678)-LDLT in the Kyushu group and 61% of LDLT with GRWR >0.8% in the Kyoto group 12,40. In contrast, PCS41 and SAL42 have been widely utilized in Western countries 17.…”
Section: Discussionsupporting
confidence: 58%
“…Authors have shown excellent outcomes even in patients with GRWR <0.8, such as left lobe grafts. 30,[41][42][43] High portal inflow and pressure across liver graft lead to graft injury and poor graft-related survival. [22][23][24][25] Studies show that PVP and GRSVR are better variables to predict the occurrence of EAD, 24,41,44 similar results were seen in our study where high ΔP post and low GRSVR were identified as factors determining EAD occurrence (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 45 papers were identified and screened. In 16 studies, the vast majority of authors reported their survival and SFSS-rates after LDLT using a cut-off for GRWR at <0.8% vs. ≥0.8% ( Table 1 ) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Most studies report a lower DFS when the liver volume is lower (i.e., GRWR < 0.8) compared to higher volumes.…”
Section: Resultsmentioning
confidence: 99%